Investigation on the dosage of assistants in preparing nano-silicate/NR composites - Guang Li; Jiang Wang; Tongjian Zhao; Xin Fu (IRRDB Conference: NR Industry: Responding to Globalization 7-8 September 2004, Kunming International Convention & Exhibition Center, China)
This experiments adopt the principle of the latex to concrete together, investigating on Na2SiO3 9H2O is made to Nano-SiO2 lotion in reaction of the hydrochloric acid with assistants and then mixes with natural rubber latex to prepare the Nano-SiO2/NR composites. Analyzing on the dosage of silane coupling agent, the surface activity agent, nucleus agent and dispersant agent effect on the properties and interface of the Nano-SiO2/NR composites, according to Orthogonal TEsting Experiments to get the best conditions of preparing Nano-SiO2/NR composites.
Keywords: Assistant; Composites; Nano-SiO2